The Ladder of Rationality - Fink, Julian (Ethical theory and moral practice, 2016)
This paper is a review and critical discussion of John Broome’s Rationality Through Reasoning. In particular, it engages critically with (i) Broome’s view on the independence of normative reasons and rationality, (ii) his construal of the capacity, property, and requirement senses of “rationality”, and (iii) his account of reasoning as a conscious, rule-following operation on mental contents.